2021
DOI: 10.1186/s13104-021-05711-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of ABCB1 (rs1128503, rs1045642) and CYP2E1 rs3813867 with the duration of tuberculosis therapy: a pilot study among tuberculosis patients in Indonesia

Abstract: Objective The risk of contracting tuberculosis (TB) and the efficacy of TB therapy are affected by several factors, including genetic variation among populations. In the Indonesian population, data on the genes involved in drug transport and metabolism of TB therapy are limited. The aim of this study was to identify the genetic profile of the ABCB1 gene (rs1128503 and rs1045642) and CYP2E1 gene (rs3813867) in Indonesians with TB. This study was a cross-sectional study of 50 TB outpatients in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…MPO induces necrosis in human neutrophils, promotes default apoptosis and subsequent phagocytosis of mycobacteria‐infected neutrophils by macrophages to control mycobacteria 52 . It was known that CST3, TGM2, ABCB1 and COCH are biomarkers in the development of TB 53–56 . Further analysis of scRNA showed that CST3, ABCB1, BSG and GRN were highly expressed in different immune cells and the remaining five hub genes might regulate the immune process in different ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPO induces necrosis in human neutrophils, promotes default apoptosis and subsequent phagocytosis of mycobacteria‐infected neutrophils by macrophages to control mycobacteria 52 . It was known that CST3, TGM2, ABCB1 and COCH are biomarkers in the development of TB 53–56 . Further analysis of scRNA showed that CST3, ABCB1, BSG and GRN were highly expressed in different immune cells and the remaining five hub genes might regulate the immune process in different ways.…”
Section: Discussionmentioning
confidence: 99%
“… 52 It was known that CST3, TGM2, ABCB1 and COCH are biomarkers in the development of TB. 53 , 54 , 55 , 56 Further analysis of scRNA showed that CST3, ABCB1, BSG and GRN were highly expressed in different immune cells and the remaining five hub genes might regulate the immune process in different ways. However, the association of these genes in TB has not been documented and more research is required.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) are a class of human genetic polymorphisms that are polymorphisms in DNA sequences caused by conversions, reversals, deletions and insertions of individual nucleotides at the genomic level [20]. It occurs in more than 1% of the population, and there is roughly one SNP for every 1000 bases in the human genome.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) are considered to be the main source of human variation. In recent years, based on genomewide linkage analysis studies, candidate gene association studies and genome-wide association analysis, we have found that host gene polymorphisms can affect the occurrence, development and outcome of TB [3]. Host gene SNPs may in uence the susceptibility and severity of the host to TB.…”
Section: Introductionmentioning
confidence: 99%